2019
DOI: 10.1186/s41038-018-0137-9
|View full text |Cite
|
Sign up to set email alerts
|

Burn image segmentation based on Mask Regions with Convolutional Neural Network deep learning framework: more accurate and more convenient

Abstract: Background Burns are life-threatening with high morbidity and mortality. Reliable diagnosis supported by accurate burn area and depth assessment is critical to the success of the treatment decision and, in some cases, can save the patient’s life. Current techniques such as straight-ruler method, aseptic film trimming method, and digital camera photography method are not repeatable and comparable, which lead to a great difference in the judgment of burn wounds and impede the establishment of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 22 publications
1
29
0
Order By: Relevance
“… 18 , 37 , 39 , 40 , 46 , 51 , 53 , 59 , 63 Further, in conditions in which there are well-established correlations between certain risk markers and an outcome of interest, such as deranged blood tests on admission and AKI in burn patients, ML yielded highly accurate predictive algorithms. 38 , 44 , 55 24 47 However, attempts to include weakly related risk markers resulted in algorithms that had an overall lower predictive accuracy, rendering them unsafe for clinical practice. This review further identified that some plastic surgery subspecialties, such as hand surgery, have yet to incorporate this technology.…”
Section: Discussionmentioning
confidence: 99%
“… 18 , 37 , 39 , 40 , 46 , 51 , 53 , 59 , 63 Further, in conditions in which there are well-established correlations between certain risk markers and an outcome of interest, such as deranged blood tests on admission and AKI in burn patients, ML yielded highly accurate predictive algorithms. 38 , 44 , 55 24 47 However, attempts to include weakly related risk markers resulted in algorithms that had an overall lower predictive accuracy, rendering them unsafe for clinical practice. This review further identified that some plastic surgery subspecialties, such as hand surgery, have yet to incorporate this technology.…”
Section: Discussionmentioning
confidence: 99%
“…Mask R-CNN is the model that has the best result, followed by the YOLOv3, MnasNet and Faster R-CNN Resnet 50 models, this can be explained because Mask R-CNN achieves good results with few images [14], unlike the others that need a dataset with more training images. Likewise, the Mask R-CNN models have better results in terms of correct detection (TP + TN) in the first than the second scenario, this can be explained because in the first scenario the models are trained with more images quantities than in the second.…”
Section: Ac =mentioning
confidence: 99%
“…However, nowadays, there are several machine learning techniques for the processing of images that have achieved high precision for a number of tasks, such as the classification of images, the detection and locating of objects, one of them is Mask R-CNN, which has achieved precisions of 97.8 %, 95.78 %, 98.5 %, and 85 % by solving problems of detection of fake images [13], detection of skin burns regions [14], detection of workers and danger zones in a building [15], and detection of breast lesions [16], respectively. So, Mask R-CNN could be used to solve DBIS.…”
Section: Introductionmentioning
confidence: 99%
“…And mean intersection-over-union was increased to 0.39, but the pixel accuracy was reduced to 0.57. Jiao et al [ 16 ] designed a deep learning segmentation framework based on the mask regions with the convolutional neural network (mask R-CNN). They labelled 1150 images with the format of the Common Objects in Context (COCO) dataset and trained the model on 1000 images.…”
Section: Related Workmentioning
confidence: 99%